GALAMOST: GPU-accelerated large-scale molecular simulation toolkit - Zhu, You-Liang; Liu, Hong; Li, Zhan-Wei; Qian, Hu-Jun; Milano, Giuseppe; Lu, Zhong-Yuan (Journal of computational chemistry, 2013)
GALAMOST [graphics processing unit (GPU)‐accelerated large‐scale molecular simulation toolkit] is a molecular simulation package designed to utilize the computational power of GPUs. Besides the common features of molecular dynamics (MD) packages, it is developed specially for the studies of self‐assembly, phase transition, and other properties of polymeric systems at mesoscopic scale by using some lately developed simulation techniques. To accelerate the simulations, GALAMOST contains a hybrid particle‐field MD technique where particle–particle interactions are replaced by interactions of particles with density fields. Moreover, the numerical potential obtained by bottom‐up coarse‐graining methods can be implemented in simulations with GALAMOST. By combining these force fields and particle‐density coupling method in GALAMOST, the simulations for polymers can be performed with very large system sizes over long simulation time. In addition, GALAMOST encompasses two specific models, that is, a soft anisotropic particle model and a chain‐growth polymerization model, by which the hierarchical self‐assembly of soft anisotropic particles and the problems related to polymerization can be studied, respectively. The optimized algorithms implemented on the GPU, package characteristics, and benchmarks of GALAMOST are reported in detail. © 2013 Wiley Periodicals, Inc. A new molecular simulation toolkit composed of recently developed force fields and specified models is presented to study the self‐assembly, phase transition, and other properties of polymeric systems at the mesoscopic scale by using the computational power of graphics processing units. The hierarchical self‐assembly of soft anisotropic particles and the problems related to polymerization can be studied by corresponding models included in this toolkit.